Use of spent domestic soybean oil by microorganisms isolated from the solid waste of the alperujo residue - Melo, Marcela Magalhães (2017)
Domestic soybean oil used in frying process comprises a kind of residue that when improperly discarded to the environment, can cause serious environmental problems, such as; fouling and plugging of pipes in the sewers network, water contamination of rivers and dams blocking the entry of light and oxygen. Negative impacts on the ground are also possible as well as the contamination of groundwater. Thus, the use as carbon source of low cost in bioprocesses as production of biomass is a cheap alternative for reuse of this oil. The alperujo is a waste generated during the processing of olive oil, and it is toxic to most microorganisms, due to high concentrations of phenols, organic load and low pH. Thus, the study of the microbiota of this residue made it possible to found microorganisms able to grow on the used soybean oil. That said, the objective of this work was to isolate and characterize the microorganisms of alperujo, as well as the production of microbial biomass, in used soybean oil. For this reason, it was carried out isolation, morphological characterization and identification by MALDI TOF of microorganisms found on alperujo. There was a predominance population of yeasts and filamentous fungi. The bacteria showed a greater diversity of Bacillus species, being the predominant genus in the samples. For biomass production, it were made treatments containing Rhodotorula mucilaginosa isolation of alperujo and with Candida rugosa CCMA 00371, both coinoculated with Bacillus subtilis CCMA 0085 in medium containing (% m/v: 0,075 glucose and 0.375 (NH4) 3 PO4) in 75 mL of water and 75 mL of reused soybean oil and in a synthetic medium YEPG as positive control. At the end of fermentation, we could observe the biomass production in both ways. The treatment with soybean oil, presented the lowest averages of biomass, but we observed changes in the chemical characteristics of soybean oil, an indication of a possible use as carbon source by microorganisms.